Analisis Yuridis terhadap Batas Kekuasaan Presiden dalam Memberikan Hak Prerogatif Berupa Abolisi (Pusat Riset dan Inovasi Nasional, 2026)
The president's prerogative is a form of power inherent in the president's position as head of state. One form of this prerogative is the granting of abolition, which is the abolition of legal proceedings against a person or group of people who are or will undergo judicial proceedings. However, in its implementation, the president's authority to grant abolition is not absolute, but is limited by the applicable legal provisions and constitutional mechanisms. This study aims to analyze the limits of the president's power in exercising the prerogative in the form of abolition and review the juridical aspects that govern the procedure and its considerations. The research method used is normative juridical research with a statutory approach and a conceptual approach. Data sources are obtained from relevant laws and regulations, legal literature, and scientific works. The results of the study show that the president's authority in granting abolition is regulated in Article 14 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which requires the president to pay attention to the considerations of the House of Representatives (DPR). Thus, this authority is not an absolute prerogative, but is limited by the principle of checks and balances in the Indonesian constitutional system. The conclusion of this study emphasizes that the restriction is a form of constitutional supervision over the use of presidential power to remain in line with the principles of the rule of law and constitutional democracy